Integrated interpretation of 3D seismic data using seismic attributes to understand the structural control of methane occurrences at deep gold mining levels: West Wits Line Goldfield, South Africa - Mkhabela, Mbali (My University, 2017)
At a number of gold mines in South Africa, the presence of methane gases has been encountered when drilling into faults and/or dyke structures extending to depths beyond 4.5 km. Methane gas has been reported to have migrated through structures from within the basin to the mine working environments (~3.0 km depths) and caused explosions. The Booysens Shale is considered one of the possible source rocks for hydrocarbons and it forms the footwall to the gold-bearing Ventersdorp Contact Reef (VCR, ~ 1.5 m thick). The Booysens Shale lies at depths between 3.5 km and 4.5 km below land surface and can be best described as the base of the divergent clastic wedge which thickens westward, hosting the quartzite and conglomerate units that sub-crop against the VCR towards the east of the gold mining areas. Geometric attributes (dip and dip azimuth) and instantaneous attributes (phase, frequency and envelope) computed for the Booysens Shale and Ventersdorp Contact Reef horizons (interpreted from 3D prestack time migrated data acquired in the Witwatersrand goldfields) provide insight into structures that extend from the Booysens Shale into the overlying mining level, the Ventersdorp Contact Reef. These attributes provide high-resolution mapping of the structures (faults, dykes, and joints) that have intersected both the Ventersdorp Contact Reef and Booysens Shale horizons. Volumetric fault analysis using the ant-tracking attribute incorporated with methane gas data also show the continuity and connections of the faults and fracture zones possibly linked to methane gas and fluid migration. Correlation between the known occurrence of fissure water and methane with geologically- and seismically-mapped faults show that steeply dipping structures (dip>60°) are most likely to channel fracture water and methane. δ13C and δ2H isotope results suggest that the methane gas (and associated H2 and alkanes) from the goldfields, particularly along seismically delineated faults and dykes, have an abiogenic origin produced by water-rock reactions. Isotopic data derived from adjacent goldfields also suggests the possibility of mixing between microbial hydrocarbons (characterized by highly depleted 2HCH4 values) and abiogenic gases. It is, therefore, possible that the propagation of these structures, as mapped by 3D seismics and enhanced volumetric attributes, between Booysens Shale and Ventersdorp Supergroup provide conduits for mixing of fluids and gases encountered at mining levels. The study may provide new evidence for the notion of hydrocarbons, particularly CH4, having migrated via faults and dykes from depth, within the Witwatersrand Basin, to where they are intersected at mining levels. The research gives new insight into mixing between microbial and abiogenic end-members within hydrogeologically isolated water pockets.
A thesis submitted to the Faculty of Science, University of the Witwatersrand in fulfilment of the requirements for the degree of Master of Science, School of Geosciences University of the Witwatersrand. 08 November 2017.
Keywords: Seismology--Methodology; Seismic reflection method; Seismic prospecting